Templateless Synthesis of Ultra‐Microporous 3D Graphitic Carbon from Cyclodextrins and Their Use as Selective Catalyst for Oxygen Activation. Issue 3 (21st January 2020) - Rendón‐Patiño, Alejandra; Santiago‐Portillo, Andrea; Vallés‐Garcia, Cristina; Palomino, Miguel; Navalón, Sergio; Franconetti, Antonio; Primo, Ana; Garcia, Hermenegildo
Abstract: Pyrolysis of α‐, β‐, and γ‐cyclodextrins at 900 °C gives rise to the formation of crystalline graphitic porous nanoparticles (GCD ), where the dimensions of the pores are uniform in the range from 0.63 to 0.97 nm, from Gα‐CD to Gγ‐CD, as determined by transmission electron microscopy. It is found that, while for Gβ‐CD and Gγ‐CD, the surface area measured by N2 adsorption is about 330–550 m 2 g −1, respectively, no area can be measured for Gα‐CD with N2 or Ar due to its small pore dimensions. However, CO2 adsorption reveals for Gα‐CD the presence of ultra‐microporosity and a surface area of 727 m 2 g −1 . GCD exhibits activity as metal‐free catalysts for the aerobic oxidation of alcohols and the activity increases as the pore dimension decreases. Density functional theory calculations indicate that this high catalytic activity for O2 activation derives from confinement effects that favor charge transfer from the graphitic walls to O2 . Studies on the formation mechanism shows that the key step leading to the formation of the channels is the melting of cyclodextrin precursors that makes possible the assembly of these capsules before their transformation into microporous graphitic particles. Abstract : Pyrolysis of cyclodextrins forms (ultra‐)microporous carbons, which are able to activate molecular oxygen. Density functional theory (DFT) calculations indicate that this high catalytic activity for O2 activation derives from confinement effects that favor charge transfer from the graphitic walls to O2 .